FINANCIAL LITERACY AMONG SELF-EMPLOYED: INITIAL FINDINGS - Maskan Md Hassan; Mohamad Nizam Jaafar; Norzitah Abdul Karim, (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2025)
This paper discusses the initial findings of financial literacy scores related to education background and financial education at the workplace among self-employed in Malaysia. The study complements knowledge of self-employed retirement planning, retirement preparedness, Islamic financial literacy, and business success. The online questionnaire that was adopted from previous literature was distributed throughout Malaysia. A total of 276 responses were received and processed for descriptive analysis. Initial findings indicated that the score differs across ethnicity and formal education attainment. While the score for those enrolling in finance and business-related courses in school, college, and university was not prominent compared with those who did not register for such classes, the increase in scoring was gradually incremental over several financial education sessions. The study implies that self-employed should pursue tertiary education after secondary school and continue attending financial education sessions at the workplace to enhance their financial literacy.